PENGARUH INVESTMENT OPPORTUNITY SET (IOS) DAN MEKANISME CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTAT DI BEI - Aulia Khanza Mariva; Zufrizal Harahap; Ramadona Simbolon (Universitas Islam Islam Sumatera Utara, 2022)
For some companies, investment activity is an important element of the company's operations and the assessment of the company's performance may be largely, or entirely dependent on the results reported in this section. The purpose of the study was to determine and analyze the effect of investment opportunity sets (IOS) and Corporate Governance mechanisms on the value of property companies listed on the Indonesian stock exchange for the 2018-2020 period. This study used 24 property sector companies for the period 2018 and 2020. The results showed that the Investment Opportunity Set (IOS) had no effect on the value of the company. This is evidenced by a significance value of .032 and a calculated t value of 1.001. Meanwhile, the significance level is smaller than the established significance level of 0.319 0.05. Therefore, the second hypothesis is not accepted because there is no positive effect of the Investment Opportunity Set on the value of the company. The Corporate Governance mechanism has no effect on the value of the company. This is evidenced by a significance value of 0.012 and a calculated t value of 0.712. Meanwhile, the significance level is smaller than the established significance level of 0.478 0.05. Therefore, the second hypothesis is not accepted because there is no potitive influence of institutional ownership on the value of the company.